Dynamics of open innovation in small- and medium-sized enterprises: A metacognitive approach - Milici, A.; Ferreira, F.; Pereira, L.; Carayannis, E.; Ferreira, J. (IEEE Transactions on Engineering Management, 2023)
Open innovation (OI) is clearly becoming increasingly important to organizations. Studying its impacts has become a challenge as assessing OI possible effects on not only performance but also processes, time, and people is difficult and complex. To move beyond these barriers, this article develops a metacognitive framework that combines cognitive mapping—supported by the strategic options development and analysis approach—and the decision-making trial and evaluation laboratory technique. This dual methodology facilitates analyses of specific OI-related impacts on small- or medium-sized enterprises (SMEs). The data were collected from SME managers and entrepreneurs who agreed to participate in an expert panel in face-to-face group meetings. The findings include that the methodologies used facilitate the identification and understanding of cause-and-effect relationships among OI determinants in SMEs, and were validated by the participants and a project manager at COTEC Portugal—Associação Empresarial para a Inovação (Business Association for Innovation). This organization is a leading think-and-action network for advancing technology diffusion and business innovation cooperation. The contributions and limitations of the proposed methodology are also analyzed.